Hubungan Aktivitas Fisik dan Pola Makan Dengan Siklus Menstruasi Pada Remaja Putri di Desa Ciherang Kab Cianjur Tahun 2024 - Oktaviani, Yayu; M, Meinasari; Septarini, Ageng (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Factors that affect the menstrual cycle in adolescents are diet, physical activity, body image, and depression together with the nutritional status of adolescent girls. Based on preliminary studies conducted in Ciherang Village, Cianjur Regency, there were 942 adolescent girls and interviews were conducted with 20 adolescent girls. 15 of these young women experienced menstrual cycle disorders and it was known that they had a poor diet and high intensity activities such as participating in extracurricular activities after school, sports, and playing.This study aims to determine the relationship between physical activity and diet with the menstrual cycle in adolescent girls in Ciherang Village, Cianjur Regency in 2024. This study used a Cross Sectional approach with a total population of 150 adolescent girls, then 109 adolescent girls were selected to be sampled using purposive sampling technique. The results showed that out of 109 respondents there were 73 participants and the rest of the irregular category there were 36 participants and it was known that as many as 62 respondents had a healthy diet while as many as 47 adolescents still had an unhealthy diet. Conclusion there is a relationship between physical activity and diet with the menstrual cycle in adolescent girls in Ciherang Village, Cianjur Regency in 2024 with a p value of .000.